STUDENTS' PERCEPTION ON THE USE OF ROLE PLAY BY TUTOR IN CLASSROOM - Ruslan, Ruslan (Siliwangi University, 2020)
The use of learning methods that are in accordance with the conditions of students is a must for teachers in order to maximize the results of the learning process. One method that can be used is role play. This study aims to determine student perceptions of learning activities followed by students who use the role play method by the teacher during the learning process in the classroom. Data is collected by using interviews with students who have carried out role play activities. Data were analyzed using thematic analysis techniques (Braun Clarke, 2006). The results show that use of role play can: (1) increase students' confidence to communicate with others, (2) increase students' ability to build language competence, (3) increase students' motivation, (4) help students eager to learn (5) motivate students to be active in learning process. Thus, students' perceptions of learning using role play show positive student perceptions.